UNDERSTANDING THE RELATIONSHIP BETWEEN CAFFEINE AND SLEEP - A REVIEW - Żaneta Kania,; Remigiusz Flakus,; Julia Szczotka,; Gabriela Szpila,; Weronika Perczyńska,; Gabriela Kapłon,; Dominika Gieroba,; Anna Kamieniak,; Artur Tumiński,; Marianna Chmiel,; Aleksandra Sokół,; Karolina Glajcar, (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: Sleep is a fundamental physiological process essential for the proper functioning of the body and mind. It supports physical restoration, emotional regulation, cognitive performance, and overall health. Due to its complexity, even slight disruptions in sleep patterns can significantly affect well-being. Caffeine is the most widely consumed psychoactive substance worldwide. Found in coffee, tea, energy drinks, and various medications, it is used daily by the majority of the population to enhance alertness and reduce fatigue. Given its popularity and stimulating properties, it is important to examine how caffeine consumption affects sleep.Methods: A comprehensive literature review was conducted, analyzing 44 studies from the PubMed database (English-language, up to 2025) that assess the relationship between caffeine and sleep.Key findings: This work reviews existing research on how caffeine intake, particularly in moderate to high doses, influences sleep timing, duration, architecture, and recovery, with a focus on timing of consumption and habitual use.Conclusions: Caffeine disrupts sleep by reducing total sleep time and altering key sleep stages, impairing recovery and daytime functioning. Even caffeine consumed hours before bedtime affects sleep quality. Limiting afternoon and evening intake is important to maintain healthy sleep. Further research is needed on individual sensitivity and long-term effects.